2010
DOI: 10.1093/carcin/bgq243
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in colorectal cancer: from benchtop to bedside

Abstract: Colon carcinogenesis represents a stepwise progression from benign polyps to invasive adenocarcinomas and distant metastasis. It is believed that these pathologic changes are contributed by aberrant activation or inactivation of protein-coding proto-oncogenes and tumor suppressor genes. However, recent discoveries in microRNA (miRNA) research have reshaped our understanding of the role of non-protein-coding genes in carcinogenesis. In this regard, a remarkable number of miRNAs exhibit differential expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 103 publications
3
104
1
Order By: Relevance
“…Lately, Hu et al (2011) as well as Humphreys et al (2013) showed that butyrate also influences miRNA expression in HCT116 and HT29 colon cancer cells, respectively. Therefore, it can act both via its function as HDI and by regulation of miRNA which are dysregulated in CRC (Bartley et al 2011;Schetter et al 2008;Slattery 2000;Wu et al 2011). In colon tumors for example, miRlet-7, miR-24, miR-34, miR-125 and miR-143 are downregulated, whereas miR-21, miR-135 and miR-106b are upregulated (Faber et al 2009;Wu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lately, Hu et al (2011) as well as Humphreys et al (2013) showed that butyrate also influences miRNA expression in HCT116 and HT29 colon cancer cells, respectively. Therefore, it can act both via its function as HDI and by regulation of miRNA which are dysregulated in CRC (Bartley et al 2011;Schetter et al 2008;Slattery 2000;Wu et al 2011). In colon tumors for example, miRlet-7, miR-24, miR-34, miR-125 and miR-143 are downregulated, whereas miR-21, miR-135 and miR-106b are upregulated (Faber et al 2009;Wu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can act both via its function as HDI and by regulation of miRNA which are dysregulated in CRC (Bartley et al 2011;Schetter et al 2008;Slattery 2000;Wu et al 2011). In colon tumors for example, miRlet-7, miR-24, miR-34, miR-125 and miR-143 are downregulated, whereas miR-21, miR-135 and miR-106b are upregulated (Faber et al 2009;Wu et al 2011). The deregulation of these miRNAs may influence the development of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, 54 miRNAs have been identified that are regulated either up or down in CRC cells relative to nontumor cells (Table 3) [69,70] . Of these, miR-17, miR-20, miR-21, miR-31, miR-92a, miR-93, miR-183 and miR-203 were upregulated in CRC cells, while miR-30a, miR-30c, miR-133a, miR-143, miR-145 were downregulated.…”
Section: In Vitro Studiesmentioning
confidence: 99%